Language shift among Muslim Tamils in the Klang Valley / Azeezah Jameelah bt. Mohamed Mohideen - Mohamed Mohideen, Azeezah Jameelah (2012)
The purpose of this study is to contribute sociolinguistic knowledge on intergenerational language shift across three age groups of Muslim Tamils in the Klang Valley area of Malaysia whose mother tongue is the Tamil language. Two research questions are investigated: (1) Is there an intergenerational decrease in the use of the Tamil language among Klang Valley Muslim Tamils in crucial domains such as family, friendship, education, entertainment, employment and social events? and (2) What are the probable motivators behind the language choices of the Klang Valley Muslim Tamils? The first question was answered through domain-based enquiry within the framework of Fishman’s domain theory (1965) and the second question was answered based on Karan’s Perceived Benefit Model of Language Shift (2001). Ninety respondents in the Klang Valley, which comprised Selangor and Kuala Lumpur, provided the principal data. With the aim of studying intergenerational language choices, these respondents were categorised into three age groups of 18 to 30, 31 to 50 and, 51 and above, with each age group corresponding to a generation. The data was collected through a triangulation of methods – questionnaires, semi-structured interviews and non-participant observation. This information was then analysed qualitatively and quantitatively for specific patterns of language use which might denote a shift away from or maintenance of the Tamil language in the Muslim Tamil community under scrutiny. Findings show sharp intergenerational decline in the use of the Tamil language from the oldest age group (first generation) to the youngest age group (third generation) in all the six domains which were examined. While the oldest age group still used its mother tongue in most of the domains, the second oldest age group used a mixture of Tamil, Malay and English and the youngest age group displayed a more pronounced use of Malay and English with Tamil being relegated to very minimal functions. This language shift over time is strongly associated with the communicative, economic, social identity and, language power and prestige motivators classified by Karan (2001). Overall, findings support a rapid intergenerational shift from the Tamil language to the Malay and English languages in this community.